Застосування інноваційних методів у природничих програмах вищої освіти у контексті міжнародних тенденцій - Когут Ержебет; Kohut Erzsébet; Kohut Erzsebet; Ленько-Teгзе Андреа; Lenyko-Thegze Andrea; Коложварі Степан; Kolozsvári István (Видавництво «Код», 2025)
Резюме. Стрімкий розвиток цифрових технологій суттєво трансформував традиційну структуру освітньої системи та похитнув усталені засади навчання. Пандемія COVID-19 не оминула освітню сферу, поставивши викладачів перед новими викликами, які вимагали швидкої адаптації до умов дистанційного та гібридного навчання. Незнайома для більшості ситуація спричинила низку питань: як ефективно розвивати знання, отримані під час лабораторних занять, формувати мануальні навички та візуальні компетенції в умовах цифрового або змішаного середовища?

Abstract. The rapid advancement of digital technologies has profoundly transformed traditional educational structures, challenging established teaching practices. The COVID-19 pandemic further accelerated this shift, compelling educators to adapt quickly by integrating digital and hybrid learning environments. This situation raises important questions regarding the effective development of laboratory-based knowledge, manual skills, and visual competencies in such settings. Technological innovations, including virtual laboratories, digital microscopy, and interactive learning materials, offer opportunities to enhance content acquisition and application. Among these innovations, the flipped classroom model has emerged as a promising approach to increase student engagement and practical competency development. This study explores the integration of the flipped classroom approach into higher education science programs. Drawing on methodological developments at the Department of Biology and Chemistry, II. Rákóczi Ferenc Transcarpathian University, the study demonstrates applications in practice-oriented courses such as cytology, histology, microbiology, and plant physiology. Concrete course module templates illustrate the use of teacher-prepared videos, digital resources, microscopic observations, and visual diagnostic skills to foster self-directed learning and analytical thinking, while maintaining the importance of in-person laboratory sessions for manual skill development. Additionally, the study addresses challenges related to implementation, including technological resistance among senior faculty, digital inequality, and data security concerns. It highlights the need for institutional and infrastructural support to ensure the successful adoption of the flipped classroom model in science education.
Application of innovative methods in higher education science programs in light of international trends
Весь випуск: https://sites.google.com/uica.education/nayka/%D0%BD%D0%B0%D1%83%D0%BA%D0%BE%D0%B2%D1%96-%D0%B7%D0%B0%D0%BF%D0%B8%D1%81%D0%BA%D0%B8-17?authuser=0
Keywords: вища освіта; flipped classroom; лабораторне навчання; природнича освіта; цифрові інновації; EDUCAUSE Horizon Report